(untitled) (Medical Forum Monthly, 2023)
Objective: Sofosbuvir (SOF) is mostly eliminated via the kidneys. Patients with varied pretreatment estimated glomerular filtration rates (eGFR) were studied to determine the effectiveness and safety of SOF-containing regimens in chronic Hepatitis C patients. Study Design: Cohort study Place and Duration of Study: This study was conducted at the AJKMC, Muzaffarabad from 01.01.2020 to 30.06.2020. Materials and Methods: Patients over the age of 18 in Pakistan who have been diagnosed with chronic HCV and whose eGFR is below 60 mL/min/1.73 m2 are included. Between 01/01/2020 to 30/06/2020, they were treated at hospital for chronic hepatitis C with SOF-based antiviral medication. Laboratory tests, an abdominal sonogram, and a clinical evaluation were performed on every patient. For the latter, CBC, transaminases, bilirubin, albumin, HCV viral load, HBsAg, creatinine, fasting plasma glucose, alpha-fetoprotein, pregnancy tests, and hemoglobin A1c were measured. Results: An initial eGFR was calculated in 100 subjects (3a genotype): The eGFR levels of 75 patients were below 30 while those of 25 patients were over 30. SVR was achieved in 90% of patients with SOF-based regimen. In 7% of the patient’s adverse effect after SOF-based regimen was observed mainly due to worsened renal functionalities. Conclusion: Treatment based on SOF proved effective and safe, causing very mild adverse effects. Larger research is still required to confirm these findings, however.